The moderating effect of external environment on the relationship between market orientation and business performance: a quantitative approach - Jabeen, Rubina; Aliyu, Mukhtar Shehu; Mahmood, Rosli (Othman Yeop Abdullah (OYA) Graduate School of Business, Universiti Utara Malaysia, 2016)
The purpose of this study is to examine the moderating role of external environment on the relationship between market orientation (MO) and business performance of small and medium enterprises (SMEs) in Punjab, Pakistan.This study seeks to resolve the inconsistencies found in the contemporary literature regarding the relationship between MO and business performance. Questionnaire using a 5-point Likert scale was adopted from previous researcher’s work to ascertain the responses of the respondents.Survey research design was adopted and self administered questionnaires were used to collect the data from SMEs.The analysis was conducted using SPSS 20.The major findings of the study indicated that market orientation has a significant relationship with business performance while external environment plays a moderating role between market orientation and business performance.